Prevalence and Outcomes of Congenital Heart Disease in Very Low Birth Weight Preterm Infants: An Observational Study From the Brazilian Neonatal Network Database. Issue 1 (6th October 2020) - Anderson, Daniela; Aragon, Davi Casale; Gonçalves-Ferri, Walusa A.; Manso, Paulo H.; Leal, Gabriela; Krebs, Vera L. J.; Caldas, Jamil P. S.; Almeida, João H. C. L.; Ribeiro, Manoel A. S.; Silveira, Rita C.; Duarte, José L. M. B.; Penido, Márcia G.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To evaluate the prevalence of congenital heart disease and their outcomes in a Brazilian cohort of very low birth weight preterm infants. Design: Post hoc analysis of data from the Brazilian Neonatal Network database, complemented by retrospective data from medical charts and a cross-sectional survey. Setting: Twenty public tertiary-care university hospitals. Patients: A total of 13, 955 newborns weighing from 401 to 1, 499 g and between 22 and 36 weeks of gestational age, born from 2010 to 2017. Interventions: None. Measurements and Main Results: The prevalence of congenital heart disease was 2.45% (95% CI, 2.20–2.72%). In a multivariate regression analysis, risk factors associated with congenital heart disease were maternal diabetes (relative risk, 1.55; 95% CI, 1.11–2.20) and maternal age above 35 years (relative risk, 2.09; 95% CI, 1.73–2.51), whereas the protection factors were maternal hypertension (relative risk, 0.54; 95% CI, 0.43–0.69), congenital infection (relative risk, 0.45; 95% CI, 0.21–0.94), and multiple gestation (relative risk, 0.73; 95% CI, 0.55–0.97). The pooled standardized mortality ratio in patients with congenital heart disease was 2.48 (95% CI, 2.22–2.80), which was significantly higher than in patients without congenital heart disease (2.08; 95% CI, 2.03–2.13). However, in multiple log-binomial regression analyses, only the presence of major congenital anomaly, gestational age (< 29 wk; relative risk, 2.32; 95% CI, 2.13–2.52), and Score for Neonatal Acute Physiology and Perinatal Extension II (> 20; relative risk, 3.76; 95% CI, 3.41–4.14) were independently associated with death, whereas the effect of congenital heart disease was spotted only when a conditional inference tree approach was used. Conclusions: The overall prevalence of congenital heart disease in this cohort of very low birth weight infants was higher and with higher mortality than in the general population of live births. The occurrence of a major congenital anomaly, gestational age (< 29 wk), and Score for Neonatal Acute Physiology and Perinatal Extension II (> 20) were significantly and independently associated with death, whereas the association of congenital heart disease and death was only evident when a major congenital anomaly was present.